REVIEWS. Issue 3 (7th December 2012) - Kruse, Nathan B.; Jo, Elisha; Veblen, Kari
YOUNG @ HEART, STEPHEN WALKER (2007) Twentieth Century Fox Film Corporation, Los Angeles, 108 minutes, rating: PGMUSICIANS AS LIFELONG LEARNERS: DISCOVERY THROUGH BIOGRAPHY, RINEKE SMILDE (2009) Delft: Eburon, 292 pp., ISBN: (10): 9059723015, ISBN: (13): 978-9059723016, p/bk, $ 30.00COMMUNITY MUSIC IN THEORY AND IN PRACTI CE, LEE HIGGINS (2012) New York: Oxford University Press, 229 pp., ISBN: 9780199777839, h/bk, $99.00, p/bk, $29.95